Digital Transformation: Implementation of the “Gesit Media” Program through Interactive Socialization for Students of SDN Sidomulyo 1 Tuban - Pramesty, Meydiana Dyah; Susanto, Rika Yuli; Komania, Nasyiatul; Afifah, Rina Mei Zul; Arrohmaany, Sholahuddin Zulfan; Nuraida, Dede (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2025)
Digital transformation in the world of education is an urgent need to equip students with 21st century skills. Community service through the